Spiritual Counseling As An Alternative Problem Solving - Wajdi, Muh Barid Nizaruddin (EDUCATIO : Journal of Education, 2016)
In Islamic doctrine, spiritual counseling has developed since some Centuries ago. Mohammad is a Counselor figure who Able to give problem-solving society for his soul. This spiritual counseling has aimed to help someone to form healthy soul with Becoming a true human, in the world and hereafter. According to counseling concept, human as a biological human being has potential basic human Determine what personality is instinct.  Quran Explains that has a human although original (nature) depend on what the potential influence of environment or a positive agent depend on the environment influences what specialty in children age